ECOG performance status ≥2 as a prognostic factor in patients with advanced non small cell lung cancer treated with immune checkpoint inhibitors—A systematic review and meta-analysis of real world data. (July 2020) - Dall'Olio, Filippo G.; Maggio, Ilaria; Massucci, Maria; Mollica, Veronica; Fragomeno, Benedetta; Ardizzoni, Andrea
Highlights: Immune Checkpoint Inhibitors (ICI) are used regardless of performance status. Randomized clinical trials (RCT) of ICIs enrolled mostly patients with ECOG PS 0 or 1. ICIs' efficacy in these patients can be extrapolated from real world data. We analysed 19 articles comprising 3600 patients, 757 of whom with PS ≥ 2 (21.0%). Our meta-analysis shows a worse outcome in patients with PS ≥ 2. Abstract: Objectives: ICIs have been approved and are routinely administered regardless of performance status (PS), despite randomized clinical trials of ICIs alone or combined with chemotherapy or target therapy enrolled patients with ECOG PS 0 or 1, while patients with ECOG PS 2 or more were excluded. Materials and methods: We carried out a meta-analysis of available clinical studies exploring the prognostic impact of PS ≥ 2 on Overall Survival (OS), Progression Free Survival (PFS) or Overall Response Rate (ORR) in patients with non small cell lung cancer (NSCLC) treated with immunotherapy (any line). Results: We reviewed 19 studies, comprising 3600 NSCLC patients, 757 of whom with ECOG PS > 1 (average 21.0%, range 6.0–48.6%). In the overall population PS ≥ 2 resulted in worse OS, PFS and ORR (OS pooled hazard ratio of 2.72; 95% CI: 2.03–3.63; I 2 72.70%, p  < 0.001; PFS pooled hazard ratio of 2.39; 95% CI 1.81–3.15, p  < 0.0001; I 2 73.03%; ORR pooled odds ratio 0.25; 95% CI 0.11–0.56, p 0.001; I 2 0.00%). Conclusion: ECOG PS ≥ 2 retains an important prognostic validity in patients treated with ICI similar, in terms of effect size, to that reported for chemotherapy in NSCLC. The high level of heterogeneity for OS and PFS analysis (but not for ORR), not completely explained by the different proportion of ECOG 3−4 patients (ranging from 0% to 50% of the PS ≥ 2 population), could be the result of both patient heterogeneity within the PS 2 population and the subjectivity of ECOG PS assessment. Whether poorer PS is also a predictor of lower immunotherapy efficacy remains still to be demonstrated.